2014
DOI: 10.1002/cbic.201402087
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Polyamine BPA‐C8 Inhibits TGF‐β1‐Mediated Conversion of Human Dermal Fibroblast to Myofibroblasts and Establishment of Galectin‐1‐Rich Extracellular Matrix in Vitro

Abstract: Cancer-associated fibroblasts (CAFs) play a role in the progression of malignant tumors. They are formed by conversion of fibroblasts to smooth muscle α-actin-positive (SMA-positive) myofibroblasts. Polyamines are known to change the arrangement of the actin cytoskeleton by binding to the anionic actin. We tested the effect of the synthetic polyamine BPA-C8 on the transition of human dermal fibroblasts to myofibroblasts induced either by TGF-β1 alone or by TGF-β1 together with adhesion/growth-regulatory galect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…As indicated above, the ACFs resemble normal dermal fibroblasts of a healthy individual stimulated by TGF-β1. Therefore, it may be hypothesized that therapeutic attenuation of TGF-β activity ( 38 , 39 ), blocking of transition of fibroblasts to myofibroblasts ( 39 ) and/or therapeutic blockade of their function ( 40 ) may be used to prevent resistance to B-Raf inhibitor therapy in the future. Mechanistically, this blockade would disrupt bi-directional cross-talk between the melanoma cells and stromal fibroblasts which allow the tumors to amplify a drug-resistant niche.…”
Section: Discussionmentioning
confidence: 99%
“…As indicated above, the ACFs resemble normal dermal fibroblasts of a healthy individual stimulated by TGF-β1. Therefore, it may be hypothesized that therapeutic attenuation of TGF-β activity ( 38 , 39 ), blocking of transition of fibroblasts to myofibroblasts ( 39 ) and/or therapeutic blockade of their function ( 40 ) may be used to prevent resistance to B-Raf inhibitor therapy in the future. Mechanistically, this blockade would disrupt bi-directional cross-talk between the melanoma cells and stromal fibroblasts which allow the tumors to amplify a drug-resistant niche.…”
Section: Discussionmentioning
confidence: 99%
“…Deregulation of the microenvironment during the wound healing results in delayed healing in venous ulcers or in diabetic foot syndrome [ 50 , 51 ]. Part of granulation tissue fibroblasts is transformed to the myofibroblasts due to activity of TGF-β1/3 and/or galectin-1 [ 52 , 53 ]. Myofibroblasts are very active in formation of extracellular matrix and contribute to the reduction of wound size by their contractibility.…”
Section: Escs and Wound Healingmentioning
confidence: 99%
“…Modification of local inflammatory environment in tumor stroma is also behind effect of drugs such as imiquimode or non-steroidal anti-inflammatory drugs. Specific targeting of CAFs is not recently in clinical use, however, early preclinical data are promising [ 53 ].…”
Section: Malignant Melanoma: Microenvironment In Non-keratinocyticmentioning
confidence: 99%
“…In addition, previous studies have revealed that galectin-1 plays a role in the desmoplastic reaction associated with PC (22). Furthermore, it has been reported that TGF-β1 alone or TGF-β1 together with galectin-1 induces the transition of human dermal fibroblasts to myofibroblasts (23) and that galectin-1 may promote the TGF-β1-induced differentiation of fibroblasts by sustaining nuclear localization of Smad2 in pulmonary fibrotic diseases (17). however, it is not known whether galectin-1 plays a fibrogenic role in CP/PC and which is the related underlying mechanism.…”
Section: Galectin-1 Expression In Activated Pancreatic Satellite Cellmentioning
confidence: 94%